THE ACQUISITION OF ENGLISH INTERROGATIVE OF A SIX-YEAR-OLD CHINESE INDONESIAN BOY - James Vivaldi; Julia Eka Rini (Institute of Research and Community Outreach - Petra Christian University, 2013)
This study focuses on language acquisition of a Chinese Indonesian multilingual boy, who understands three languages, English, Indonesian and Chinese, although his English seems to be dominant than others. This qualitative research was conducted to assess how his English develops. The two questions of this study are, first, how his acquisition of English question has developed, and second, what the difficulties for him to make question in English are. The result of the study is that the boy is at the third stage, a period when a child get accustomed to use auxiliary and inversion and his difficulties are in the area of vocabulary, tenses and inversion of embedded question.